Deciphering the dual role of autophagy in gastric cancer and gastroesophageal junction cancer: from tumor suppression to cancer progression - Lili Lei; Junling Zhang; Ran Wei; Bingqi Dong; Xin Wang; Ying Zhou (Discover Oncology)
Abstract Autophagy is a fundamental cellular process responsible for breaking down and recycling damaged organelles and proteins, thereby maintaining cellular homeostasis. Under stress conditions, autophagy is upregulated to restore cellular equilibrium. However, excessive activation of autophagy can lead to cell death. The interplay between autophagy and cell death pathways is highly complex, with disturbances in autophagic activity contributing to disease development. Notably, autophagy plays a critical role in the pathogenesis and progression of cancer, tightly regulating tumour cell behavior. Gastric cancer (GC) ranks as the fifth leading cause of cancer-related mortality worldwide. Among its subtypes, gastroesophageal junction cancer (GEJC) stands out due to its prevalence in both developed and developing countries. Autophagy has a dual and dynamic role in GC and GEJC, capable of acting as both a tumour suppressor and a tumour promoter, depending on various context-specific factors including the tumour stage, microenvironment, and genetic alterations. Emerging evidence highlights the involvement of autophagy in modulating the therapeutic response of GC and GEJC cells, emphasizing its potential as a promising target for cancer therapy. Autophagy-related genes (ATGs) and other regulatory proteins are pivotal in controlling the progression of GC and GEJC, serving as valuable biomarkers for diagnosis and treatment strategies. Additionally, autophagy influences tumour initiation and reshapes the tumour microenvironment in GC and GEJC. Graphical Abstract Mechanisms of interaction between autophagy and gastric cancer/gastro-oesophageal junction cancer (GC/GEJC) and the effect of autophagy process on tumour biological behaviour